Meanings and Functions of the Ruler's Image in the Mediterranean World (11th - 15th Centuries) - Bacci, Michele; Studer-Karlen, Manuela (The Medieval Mediterranean, 2022)
The book investigates, from different methodological viewpoints, the multiple ways in which medieval rulers in different areas of the Mediterranean constructed their outward appearance and communicated it by means of a variety of rituals, object-types, and media. ; Readership: This book is meant basically for an academic audience, but it could also be of relevance to a wider public interested in the following fields: medieval art and history, Mediterranean studies, and intercultural contacts in the Middle Ages.